2014
DOI: 10.1002/qua.24648
|View full text |Cite
|
Sign up to set email alerts
|

Guest–host interaction in an aza crown analog

Abstract: Host–guest interactions in a new aza crown analog [normalN4normalC2normalH2]42− with alkali and alkaline earth metal ions are studied at different levels of theory. All the compounds are optimized at B3LYP/6‐311+G(d) level of theory. To build the general idea about the consequence of methods of computation on the interaction energy of metal ions with the ligand, geometry optimization of some selected planar systems are carried out at the M05‐2X, PBE0, wB97XD, and B3LYP‐D levels. Calculated geometrical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Recently, Lu et al have reported the entrapment of Mg 2 inside cyclo[18]carbon [29]. Similarly, Chattaraj and co‐workers reported the trapping of Mg 2 inside C 60 cage, which resulted in the formation of electrode [30]. Some properties of these Group 2 atoms and their dimers are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lu et al have reported the entrapment of Mg 2 inside cyclo[18]carbon [29]. Similarly, Chattaraj and co‐workers reported the trapping of Mg 2 inside C 60 cage, which resulted in the formation of electrode [30]. Some properties of these Group 2 atoms and their dimers are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the endohedral encapsulation of noble gas dimer inside the cavitand of cucurbit[6]uril and octa acid has been reported ( Pan et al, 2015 ; Chakraborty et al, 2016 ). Theoretically, Das and Chattaraj (2014) studied the encapsulation of alkali and alkaline earth metals inside an aza crown analogue, [(N 4 C 2 H 2 ) 4 ] 2- and the bonding interactions therein.…”
Section: Introductionmentioning
confidence: 99%